Assessing Service Quality of a Type C Passenger Terminal Using Importance–Performance Analysis: A User-Based Approach - Fitri Sari; Yusria Darma; Mubarak Mubarak; Ahyin Bilhuda Dasopang (Popular Scientist, 2026)
As a passenger terminal, Lueng Bata Mini-Bus Terminal in Banda Aceh serves as a vital hub for regional mobility and local economic activities. However, the increasing volume of users has highlighted several service-related shortcomings, including inadequate facilities, poor sanitation, and the lack of accurate departure information. This study aims to evaluate the terminal’s service quality from the users' perspective using the Importance-Performance Analysis (IPA) method. Primary data were collected through 250 respondents comprising passengers, drivers, local business operators, and community members who interact with the terminal. The findings reveal a Level of Suitability score of 78.561%, indicating that current service delivery falls short of user expectations. Several service attributes most notably, the availability of services information and the clarity of evacuation routes were identified as critical weaknesses that require immediate attention. These attributes were categorized in the IPA matrix as high-priority areas for improvement. The findings provide empirical evidence to support terminal upgrading decisions, particularly the need to align terminal status with actual service deman, with the ultimate goal of aligning operational performance more closely with user needs and expectations.